EVALUATION OF INSECTICIDES FOR THE MANAGEMENT OF BIHAR HAIRY CATERPILLAR, SPILOSOMA OBLIQUA WALK. (LEPIDOPTERA: ARCTIIDAE) IN BLACK GRAM (VIGNA MUNGO L.) - MANDAL, DIPAK; BHOWMIK, PARAMITA; BARAL, KANCHAN (The Bioscan, 2013)
An experiment was conducted at Institute of Agriculture (Palli Siksha Bhavana) farm, Visva-Bharati, Sriniketan, Birbhum, West Bengal during the summer season of 2008 to study on the evaluation of insecticides for the management of bihar hairy caterpillar (Spilosoma obliqua Walk.) in black gram. Insecticides used in the experiment were azadirachtin 1500ppm @3ml/l, endosulfan 35EC @ 300g a.i/ha, triazophos 40 EC @ 250g a.i/ha, thiamethoxam 25 WG @ 40g a.i/ha, ë-cyhalothrin 5 EC @ 40g a.i/ha, indoxacarb 14.5 SC @ 75g a.i/ha and imidacloprid17.8 SL @ 30g a.i/ha. Two sprays of insecticides were applied at fifteen days interval. The most effective insecticide in controlling the borers was triazophos followed by ë-cyhalothrin. Per cent reduction of hairy caterpillar over untreated plot after final sprays was followed this order of efficacy: triazophos (90.64%) >ë-cyhalothrin (83.71%) >indoxacarb (78.76%) >endosulfan (69.53%) >imidacloprid (62.31%) > thiamethoxam (57.40%). Azadirachtin was found to be least effective in controlling of hairy caterpillar. Highest cost benefit ratio (1:21.69) was observed in triazophos 40 EC @ 250g a.i/ha.